The isolation of rabies virus from insectivorous bat, Histiotus velatus, captured in the state of Santa Catarina (South of Brazil) - Amorim, Adalvio Fernandes de; Silva, Renato Augusto da; Silva, Norma Moraes da (Pesquisa Agropecuaria Brasileira, 2014)
Rabies virus was isolated from the brain of an insectivorous bat, Histiotus velatus Geoffroy, captured in the Municipality of Alfredo Wagner, State of Santa Catarina (South Brazil). The brain suspension was inoculated into adult mice by intracerebral route. The virus strain was identified as rabies virus by the presence of Negri bodies in the cytoplasm of nervous cells from brains of mice inoculated at 21 days of age. Identification was made by neutralization test using a standard rabies immune serum and by fluorescent antibody technique.